Birokrasi, Birokrat, dan Kultur Birokrasi Indonesia:Upaya Pemahaman tentang Tipologi Aparatur Negara dan Strategi Pengembangan Birokrasi Indonesia ke Depan - Zed, Mestika (TINGKAP, 2012)
Lack of political commitment has been considered as a principal reason for the failure of bureacratic reform, and is part of the past existing power. The failure of repeated reform attempts has indeed its roots in Indonesia’s unusual political system, in which traditional and colonial ruling system have still influenced power in recent practices. Prospects for reform therefore depend either on fundamental political change, or on generating public surveillance to the system as well to those rulers, who fear that reform represents a threat to their interests. What are factors determine a government’s commitment to implement bureauratic reform? How can we identify genuine commitment and generate increased political will where it is lacking? This article from historical point of view traces the bureaucrat’s typologies that had have been used in Indonesia in order to highlight the key elements of main obstacles in bureacratic reform and the means available for implementing good and clean government apparatus whose commitment is weak. It argues that strong political leadership and irrevocable bureaucratic reform policies are key factors in assuring implementation, while pressures from public media can help foster commitment.